EFEKTIVITAS PEMBERIAN JUS KURMA KELAPA TERHADAP PENINGKATAN KADAR HB PADA REMAJA PUTRI DENGAN ANEMIA - Silalahi, Yulia Yolanda Gracia; suswati (Poltekkes Kemenkes Medan, 2021)
Anemia in adolescent girls is a problem faced by Indonesian adolescents by 12% of boys and 23% of girls, including in the district of Deli Serdang. As many as 68.79% of adolescent girls in Deli Serdang have experienced menstruation, this indicates a higher risk of anemia. In dealing with adolescent anemia, coconut date juice is a good alternative. Dates contain iron 6.0mg/100g dates and coconuts contain vitamin C as much as 3.4mg/100ml, iron can be absorbed well by the body if assisted with vitamin C, therefore the combination of coconut date juice is very good for treating anemia. The type of research used was quasi-experimental with a one group pretest-posttest approach without control design. This study aims to determine the effectiveness of coconut date juice provision to adolescent girls with anemia in hamlet VIII, Marindal II Village. The sample in this study amounted to 20 girl. The research instrument used was an observation sheet. Data analysis used univariate and bivariate analysis. The results obtained in the conclusion of the study were the effectiveness of coconut date juice in increasing Hb levels in adolescents with p value = 0.000 with an average level of increase of 3.3gr/dl.